Alexander B. answered • 10/21/13

Experienced and Enthusiastic Math Tutor

Start with the innermost parentheses => (2-3x)

Plug in x and you'll get (2 - 3) which is (-1)

Proceed to the next level of brackets => [x - (-1) - 4]

Subtracting a negative is the same as adding the positive => [x + 1 - 4]

Simplify to [x + (-3)], since 1 - 4 is (-3). You could also just write [x - 3]

Plug in x and you'll get [1 - 3] which is (-2)

Don't forget the 2 outside the brackets

2 * (-2) =

**(-4)**Solve for the second function x - 5

Plug in x and you'll get 1 - 5 which is

**(-4)**(-4) = (-4)

:D